Pelatihan Instalasi dan Penataan Sistem Tata Suara Masjid - Taufik, Mochammad; Hudiono; Aisah; Hariyadi, Aad; Perdana, Ridho Hendra Yoga; Rakhmania, Amalia Eka (AJAD : Jurnal Pengabdian kepada Masyarakat, 2021)
Mosques are one of the places where community activities are concentrated in the religious field, especially in Indonesia where the majority of the population is Moslems. The mosques are also important means of spreading religion, due to the close location and spread out in the community. The arrangement of the sound system in a mosque is one of the vital things to support religious activities. The purpose of this activity is to provide training on the installation and arrangement of sound systems at the Darul Muttaqin Mosque, Kedungkandang District, Malang. Training is given to mosque takmirs so that they can install and maintain sound systems in mosques. The result of this training was that the sound system of the mosque which was initially bad due to a buzzing sound and did not clearly convey the information provided became clearer and no longer disturbed the congregation or local residents. When there is a sound system problem, takmir can repair it directly without the need to wait for a technician so that religious activities and messages run smoothly.